Decreasing Nicotine Content Reduces Subjective and Physiological Effects of Smoking - David M. Penetar; Kimberly P. Lindsey; Erica N. Peters; Trisha M. Juliano; Scott E. Lukas (SAGE Publishing, 2012)
Objective Assessment of the subjective and physiological effects of smoking cigarettes with different machine-smoked nicotine yields. Methods Eight volunteers rated the characteristics of cigarettes with varying levels of nicotine (Quest ® ). At 30 minute intervals, participants smoked one of three different Quest ® brand cigarettes in a counterbalanced order (reported machine-smoked nicotine yield: 0.6 mg, 0.3 mg, or 0.05 mg). Smoking satisfaction and sensations were measured on a cigarette evaluation questionnaire. A mood questionnaire measured self-reported subjective changes in 'happy', 'stimulated', 'anxious', 'desire to smoke', and 'desire not to smoke'. Heart rate and skin temperature were recorded continuously. Results As nicotine yield decreased, cigarettes produced smaller changes in subjective ratings on the evaluation questionnaire with the placebo nicotine cigarette always rated lower or less potent than the other two cigarettes evaluated. Heart rate was significantly increased by the reduced nicotine cigarettes, but was not affected by the nicotine-free cigarette. Conclusion These results indicate that machine-smoked yield is an important determinant of both the subjective and physiological effects of smoking. The use of reduced and nicotine free cigarettes in smoking cessation programs remains to be evaluated.